Aldose Reductase B1 in Pig Seminal Plasma: Identification, Localization in Reproductive Tissues, and Relationship With Quality and Sperm Preservation - Mateo-Otero, Yentel; Viñolas-Vergés, Estel; Llavanera, Marc; Ribas-Maynou, Jordi; Roca, Jordi; Yeste, Marc; Barranco, Isabel (Frontiers in Cell and Developmental Biology, 2021)
Aldose Reductase B1 (AKR1B1), a NADPH-dependent enzyme that belongs to the aldo-keto reductase protein superfamily, has been reported to be involved in both male and female reproductive physiology. The objectives of this study were: (1) to evaluate the concentration of SP-AKR1B1 in pig ejaculate fractions; (2) to describe the immunohistochemical localization of AKR1B1 alongside the boar genital tract; (3) to evaluate the relationship between SP-AKR1B1 and sperm quality/functionality parameters. Ejaculates from seven boars (one ejaculate per boar) were collected in separate portions (the first 10 mL of the sperm rich fraction [SRF-P1], the rest of the SRF [SRF-P2], and the post-SRF [PSRF]) and the concentration of SP-AKR1B1 was assessed using an Enzyme-Linked Immunosorbent Assay (ELISA). Immunohistochemistry and immunoblotting targeting was conducted in the reproductive tissues of these boars. Additionally, the entire ejaculates of 14 boars (one ejaculate per boar) were collected and split into three separate aliquots for: i) SP-AKR1B1 quantification; ii) assessment of sperm concentration and morphology; and iii) evaluation of sperm quality and functionality parameters upon ejaculate collection (0 h) and after 72 h of liquid storage at 17 ºC. Concentration of AKR1B1 in the SP of SRF-P1 (458.2 ± 116.33 ng/mL) was lower (P<0.05) than that of SRF-P2 (1105.0 ± 229.80 ng/mL) and PSRF (1342.4 ± 260.18 ng/mL). Monomeric and dimeric AKR1B1 forms were expressed alongside the reproductive tissues, except in the bulbourethral glands. No relationship between SP-AKR1B1 and sperm quality/functionality parameters was observed either at 0 h or after 72 h of storage at 17 ºC. In conclusion, AKR1B1 is expressed in the reproductive organs of boars (except bulbourethral glands) and its highest concentration is found in the PSRF, suggesting that seminal vesicles would be the main secretory source. However, this enzyme does not appear to be related to sperm quality/functionality or to the sperm ability to withstand liquid storage at 17 ºC.